RECONCEPTUALIZING LISTENING IN TASK-BASED LANGUAGE TEACHING: FROM PASSIVE RECEPTION TO ACTIVE UNDERSTANDING - Mardona Rakhimova (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Introduction Listening has traditionally been viewed as a passive, receptive skill in language education. In many classrooms, learners listen to recordings and answer comprehension questions, with success measured by the number of correct responses. Such practices often reduce listening to a testing activity rather than recognizing it as a dynamic cognitive process. However, contemporary approaches to second language acquisition suggest that listening should be understood as active meaning construction. Task-Based Language Teaching (TBLT) provides a framework for this reconceptualization. Instead of treating listening as isolated input, TBLT embeds it within meaningful tasks that require learners to achieve specific communicative outcomes. This paper argues that listening should move from passive reception toward active understanding through task-based pedagogy. The discussion explores theoretical foundations, cognitive dimensions, pedagogical applications, and implications for academic and professional contexts.